Community Diagnosis Report on Reducing New Cases of Toddler Malnutrition Through Primary Health Care Interventions - Fauzy, Sely Nur; Rebecca, Rebecca; Negara, Tahta Rajesa Bihi Jaya Putra; Ayuningtami, Diajeng; Ernawati, Ernawati (Transpublika Publisher, 2025)
This study aims to reduce the number of new cases of malnutrition in the working area of Kresek Primary Health Center by identifying priority locations, analyzing main causes, formulating short-term solutions, and evaluating the results of interventions that have been implemented. A mini survey was conducted for data collection, followed by community problem analysis using the ‘Blum’ paradigm, then problem priorities were determined using the Delphi method. The root causes of problems were identified using a fishbone diagram. Based on the Blum paradigm, lifestyle was identified as the main problem. Interventions were carried out in the form of pre-test, post-test, and counseling on nutrition as well as training on food creation and balanced nutrition menu planning. Pre-test results showed <70 scores for 24 (80%) participants. Post-test results ≥70 were obtained by 30 (100%) participants. The activity results were declared successful because >80% of participants obtained scores ≥70. The results obtained from food creation training and balanced nutrition menu planning for toddlers showed that all participants were able to practice properly and correctly. The cause of increased new cases of malnutrition in the working area of Kresek Primary Health Center is lifestyle factors. Counseling is expected to increase knowledge of malnutrition and balanced nutrition in toddlers so that malnutrition cases can be resolved and prevented.